1997
DOI: 10.1542/peds.99.3.338
|View full text |Cite
|
Sign up to set email alerts
|

Risk Status at Discharge and Cause of Death for Postneonatal Infant Deaths: A Total Population Study

Abstract: These findings suggest that the etiology of postneonatal mortality is heterogeneous, with significant complexity in attributing specific causes of death and making designations of "preventability." The vast majority of infants who died of prematurity-related postneonatal causes never left the hospital, and only a small percentage of all infants that left the hospital before death were identified as being at high medical risk. Therefore, strategies for further decreasing postneonatal mortality must link high-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
0
11
0
2
Order By: Relevance
“…7 In a study by Stewart and Hersh 2 of an 11-year trend in neonatal mortality at Kosair Children's Hospital in Louisville, KY, it was found that neonatal mortality due to congenital malformations had not decreased despite a decrease in overall neonatal mortality. These studies suggest that, although technologic and therapeutic advances in perinatal and newborn care have contributed to decreases in neonatal morbidity and mortality, mortality rates in infants with major congenital malformations have not been significantly altered.…”
Section: Discussionmentioning
confidence: 99%
“…7 In a study by Stewart and Hersh 2 of an 11-year trend in neonatal mortality at Kosair Children's Hospital in Louisville, KY, it was found that neonatal mortality due to congenital malformations had not decreased despite a decrease in overall neonatal mortality. These studies suggest that, although technologic and therapeutic advances in perinatal and newborn care have contributed to decreases in neonatal morbidity and mortality, mortality rates in infants with major congenital malformations have not been significantly altered.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is 1 of a few population-based studies to investigate postdischarge mortality in VLBW infants. [13][14][15] Population-base studies in contrast to single institutions' experience [15][16][17][18] are larger and more representative, and their findings may be generalized. Two previous studies from the 1980s focused on center-specific mortality rates after NICU discharge, reporting a ninefold and sevenfold excess in postneonatal mortality among NICU graduates compared with non-NICU graduates.…”
Section: Discussionmentioning
confidence: 99%
“…Further, longer lives imply more opportunities for exposure to acute episodes. Kempe et al 25 report that "the vast majority of infants who died of prematurityrelated postneonatal causes never left the hospital, and only a small percentage of all infants who left the hospital before death were identified as being at high medical risk. "…”
Section: The Descriptive Epidemiology Of Infant Mortalitymentioning
confidence: 99%